2010
DOI: 10.1111/j.1399-0012.2009.01071.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and clinical predictors of primary opportunistic deep cutaneous mycoses in solid organ transplant recipients: a multicenter cohort study

Abstract: Primary deep cutaneous opportunistic mycoses in OTR occur mainly in the first two yr after transplantation, in renal transplant recipients, and in older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 28 publications
1
42
2
2
Order By: Relevance
“…In the available literature, similarly to our study, KS is more likely to develop in males [12]. Lesions were observed 2 and 9 months post-transplantation, consistently with previous observations which showed that most of the changes appear within 2 years after transplantation [30, 32]. …”
Section: Discussionsupporting
confidence: 91%
“…In the available literature, similarly to our study, KS is more likely to develop in males [12]. Lesions were observed 2 and 9 months post-transplantation, consistently with previous observations which showed that most of the changes appear within 2 years after transplantation [30, 32]. …”
Section: Discussionsupporting
confidence: 91%
“…138 In a Sardinian study, 23% of patients who were HHV-8 positive before transplantation developed KS. 139 The incidence of KS among renal transplant recipients may be 3.6% or higher in regions endemic for KS, as compared to the 0.4% incidence in renal transplant recipients in the United States and western Europe.…”
Section: Iatrogenic Ksmentioning
confidence: 99%
“…The median number of treated lesions per patient was 5 (range Q1-Q3: 3-6). Before treatment, the median tumor area per patient was 1658 mm 2 (range Q1-Q3: 399-2365) and median sum of the infiltration score per patient was 5 (range Q1-Q3: [3][4][5][6][7][8].…”
Section: Study Patientsmentioning
confidence: 99%